Оптимальное управление гребными электродвигателями электроходов при реверсировании - Яровенко, В.А.; Черников, П.С.; Варбанец, Р.А.; Зарицкая, Е.И. (Електротехніка і електромеханіка, 2018)
Целью работы является поиск оптимальных законов управления гребными электродвигателями (ГЭД) судов с электродвижением. Критериями оптимальности выбраны показатели, характеризующие маневренные свойства электроходов. Методика. Пропорциональный закон управления ГЭД не обеспечивает нужные маневренные свойства электроходам. Оптимальные законы управления ГЭД, обеспечивающие наилучшие маневренные характеристики электроходов могут быть найдены при совместном рассмотрении гребной электроэнергетической установки, гребных винтов и корпуса судна. Результаты. Предложен новый способ формирования оптимальных законов управления. Выявлен характер целевых функций и разработан метод оптимизации. Проведены оптимизационные расчеты и найдены оптимальные законы управления гребными электродвигателями при реверсе электроходов. Оптимизация проведена по критериям минимума тормозного пути и минимума расхода энергии. Проиллюстрирована эффективность использования предлагаемых законов управления. Научная новизна. Метод поиска оптимальных законов управления построен по системному принципу. Это позволяет находить законы управления гребными электродвигателями по конечному результату – по показателям судна. Практическая значимость. Предложенные рекомендации могут использоваться как при проектировании гребных электроэнергетических установок, так и при их эксплуатации. Для конкретного электрохода, в зависимости от показателей качества маневрирования, может быть выбран (из предложенных) и заложен в систему регулирования наилучший закон управления гребными электродвигателями. Метою роботи є пошук оптимальних законів управління гребними електродвигунами (ГЕД) суден з електрорухом. Критеріями оптимальності обрані показники, що характеризують маневрені властивості електроходів. Методика. Пропорційний закон управління ГЕД не забезпечує потрібні маневрені властивості електроходів. Оптимальні закони управління ГЕД, що мають забезпечити найкращі маневрені характеристики електроходів, можуть бути знайдені при спільному розгляді гребної електроенергетичної установки, гребних гвинтів і корпусу судна. Результати. Запропоновано новий спосіб формування оптимальних законів управління. Виявлено характер цільових функцій і розроблено метод оптимізації. Проведено оптимізаційні розрахунки і знайдені оптимальні закони управління гребними електродвигунами при реверсі електроходів. Оптимізація проведена за критеріями мінімуму гальмівного шляху і мінімуму витрат енергії. Проілюстровано ефективність використання запропонованих законів управління. Наукова новизна. Метод пошуку оптимальних законів керування побудовано за системним принципом. Це дозволяє знаходити закони управління гребними електродвигунами за кінцевим результатом – за показниками судна. Практична значимість. Запропоновані рекомендації можуть використовуватися як при проектуванні гребних електроенергетичних установок, так і при їх експлуатації. Для конкретного електроходу, в залежності від показників якості маневрування, може бути обрано (із запропонованих) і закладено в систему керування найкращий закон управління гребними електродвигунами. Introduction. Reliability and safety of electric ships’ maneuverability depends on the maneuvering characteristics of their propulsion motors (PM). Therefore, the issues of improving the process of controlling propulsion motors at maneuvers are topical. The aim of this paper is to find the optimal laws of control. The indicators estimating electric ships’ maneuvering properties are chosen as criteria of optimality. Methodology. A proportional control law is traditionally used in electrical propelling plants with frequency-controlled PM. However, it does not provide the necessary maneuvering characteristics to the electric ships, since it does not take into account the process of the vessel's movement. To search for the optimal control laws of propulsion motors at maneuvers, the electrical propulsion plant is considered in unity with all the components of the ship’s propulsion complex. The dimensionless parameters of the complex are revealed from the mathematical model of the transient modes of its operation. They determine the numerical values of the optimality criteria. Control signals are formed by frequency and voltage. A method for the formation of optimal control laws is proposed. The nature of the target functions is revealed and a special optimization method is developed. A minimum of the braking distance and a minimum of energy spent on maneuvering are taken as criteria of optimality. Results. The parameters of the complexes that significantly affect the optimality criteria are revealed. For various combinations of the values of these parameters, optimization calculations have been carried out and the optimal control laws of the propulsion motors during electric ships’ reversal have been found. Optimization is carried out by the criterion of the minimum of the braking distance and by the criterion of minimum energy consumption. The results are presented in an analytical form and in a graphical form. The effectiveness of the proposed control laws is illustrated. Scientific novelty. The method of searching for the optimal control laws of the propulsion motors is constructed according to the system principle. This allows us to find the control laws of the propulsion motors on the final result – on the indicators of electric ships’ maneuverability. The proposed recommendations cover a wide class of vessels with electric motion. Practical value. The proposed optimal control laws for propulsion motors can be used both in the design of propulsion power plants and in their operation. The best control law can be selected and incorporated into the control system for any particular electric ship of the considered class, depending on the quality of maneuvering. In particular, the optimal control law for propulsion motors during reversal providing electric ship’s minimum braking distance or minimum energy consumption for maneuvering can be chosen.